Multilayer antireflection optical coatings based on Nb, Si and Al oxides for nonlinear ZnGeP2 crystals - Zinoviev, Mikhail M.; Yudin, Nikolay N.; Olshukov, Alexey S.; Davydova, Alexandra Yu (Proceedings of SPIE)
The effect of the designed antireflection coatings based on Nb2O5/Al2O3 and Nb2O5/SiO2 pairs of materials on the laser-induced damage threshold (LIDT) of ZnGeP2 crystals at a wavelength of 2097 nm is shown. The coating was applied using the ion-beam sputtering (IBS) method. The LIDT of the sample coated with Nb2O5/SiO2 was W0d = 1.8 J/cm2. The LIDT of a sample coated with Nb2O5/Al2O3 is W0d = 2.35 J/cm2. The presence of silicon conglomerates in the antireflection coating leads to a decrease the LIDT of a nonlinear crystal due to local thermomechanical stresses and scattering of the incident laser radiation.